ALETHEIA: KATALISATOR PUBLIKASI ILMIAH BERBASIS OPEN JOURNAL SYSTEM (OJS) - Saksono, Herie; Utami, Karina Juniarti (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
The turbulence of technological advancements in the digital era has transformed various aspects of life, including scientific publications, which have become a determining factor in decision-making processes. Although the global trend towards open access presents significant opportunities for academics, there remains a gap between potential and realization in the field, particularly among students and faculty. This Community Service Program (PKM) aims to provide a credible scientific publication platform, enhance the quality and quantity of publications, facilitate the fulfillment of the Tri Dharma of Higher Education, expand the visibility of research outputs, and hone students' skills in writing and publishing scientific works. The implemented method encompasses the development of a journal using the Open Journal System (OJS), capacity building of human resources in scientific writing, and strengthening of content, impact, and sustainability. The result of this PKM is the establishment of "ALETHEIA: Journal of Social-Humanities, Innovation, Economics, and Education (JSHIEE)" based on OJS, which has successfully published six scientific articles authored by students. The development of this journal has yielded positive impacts, including an increase in the number and quality of scientific publications, efficiency in journal management processes, enhanced visibility of research results, and the formation of a more dynamic and collaborative research ecosystem. In conclusion, this initiative not only supports the fulfillment of the Tri Dharma of Higher Education but also contributes to improving the quality and visibility of institutional research outputs. Recommendations for further development include mentoring programs, utilization of artificial intelligence technology, initiation of international collaborations, development of digital marketing strategies, implementation of a comprehensive reward system, and provision of translation and proofreading services.